2015
DOI: 10.1109/led.2015.2496359
|View full text |Cite
|
Sign up to set email alerts
|

A 0.27e-rms Read Noise 220-μV/e-Conversion Gain Reset-Gate-Less CMOS Image Sensor With 0.11-μm CIS Process

Abstract: A low temporal read noise and high conversion gain reset-gate-less CMOS image sensor (CIS) has been developed and demonstrated for the first time at photoelectron-counting-level imaging. To achieve a high pixel conversion gain without fine or special processes, the proposed pixel has two unique structures: 1) coupling capacitance between the transfer gate and floating diffusion (FD) and 2) coupling capacitance between the reset gate and FD, for removing parasitic capacitances around the FD node. As a result, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(19 citation statements)
references
References 11 publications
(14 reference statements)
1
18
0
Order By: Relevance
“…According to the typical conversion gain of 67 µV/e-for the case of a low-noise wide dynamic range image sensor [9], the error due to the ADC nonlinearity is less than 0.066e-. If the pixel has higher conversion gain like in [15], that is 220 µV/e-, the corresponding error due to the ADC nonlinearity can be less than 0.02e-. The maximum INL of 1,200 LSBs corresponds to 0.57% of the 38.6% of 19-bit full scale code (¼ 211;600).…”
Section: Simulation and Measurement Resultsmentioning
confidence: 99%
“…According to the typical conversion gain of 67 µV/e-for the case of a low-noise wide dynamic range image sensor [9], the error due to the ADC nonlinearity is less than 0.066e-. If the pixel has higher conversion gain like in [15], that is 220 µV/e-, the corresponding error due to the ADC nonlinearity can be less than 0.02e-. The maximum INL of 1,200 LSBs corresponds to 0.57% of the 38.6% of 19-bit full scale code (¼ 211;600).…”
Section: Simulation and Measurement Resultsmentioning
confidence: 99%
“…Studies have shown [5] that for a practical single-photon imager with negligible error rate the ENC must be below 0.15 e-RMS. Recent advances in CMOS image sensor (CIS) technology have reduced the readout noise significantly, and CIS with ENC below 0.3 e-RMS have been reported [6]- [8]. These developments are due to the increase of the conversion gain of the sensors above 200 µV/e-by the use of special design and processing techniques, as well as by improvements to the noise performance of MOSFETs.…”
Section: Introductionmentioning
confidence: 99%
“…The QLog pixel will exhibit a composed linear–logarithmic photo-electric response. The paper published at IISW2017 [7] indicates that this QLog pixel can be an elegant solution to overcome the too-low integration well capacity in actual high-sensitivity, subelectron readout noise sensors [8,9,10,11,12]. …”
Section: Introductionmentioning
confidence: 99%